An Insight into the Sialomes of Bloodsucking Heteroptera - José M. C. Ribeiro; Teresa C. Assumpção; Ivo M. B. Francischetti (Psyche: A Journal of Entomology)
Saliva of bloodsucking arthropods contains dozens or hundreds of proteins that affect their hosts' mechanisms against blood loss (hemostasis) and inflammation. Because acquisition of the hematophagous habit evolved independently in several arthropod orders and at least twice within the true bugs, there is a convergent evolutionary scenario that creates a different salivary potion for each organism evolving independently to hematophagy. Additionally, the immune pressure posed by their hosts creates additional evolutionary pressure on the genes coding for salivary proteins, including gene obsolescence, which opens the niche for coopting new genes (exaptation). In the past 10 years, several salivary transcriptomes from bloodsucking Heteroptera and one from a seed-feeding Pentatomorpha were produced, allowing insight into the salivary potion of these organisms and the evolutionary pathway to the blood-feeding mode.